Розвиток фізичних основ термометрії із застосуванням нових чутливих елементів термоперетворювачів - Крайовський, Володимир Ярославович (Національний університет "Львівська політехніка", 2019)
Наведено обґрунтування та нове вирішення важливої науково-прикладної проблеми розвитку фізичних основ термометрії шляхом запровадження нових чутливих елементів засобів вимірювання температури та методів моделювання їхніх характеристик, отриманих на основі новітніх термометричних матеріалів з покращеними метрологічними та експлуатаційними характеристиками. Запропоновано концепцію моделювання та отримання термічно стійких чутливих елементів засобів вимірювання температури на основі новітніх термометричних матеріалів шляхом розроблення методу ітераційного моделювання структурних, енергетичних, термодинамічних та кінетичних характеристик чутливих елементів термоперетворювачів з урахуванням результатів експериментальних вимірювань. Розвинуто метод моделювання кінетичних характеристик нових чутливих елементів термоперетворювачів у широкому температурному діапазоні. Встановлено закономірності функцій перетворення чутливих елементів засобів вимірювання температури на основі новітніх термометричних матеріалів у температурному діапазоні 4,2÷1300 К з покращеними метрологічними характеристиками. Розвинуто метод отримання термоелектричної пари термоелектричного термометра, обидві вітки якої виготовлені з новітніх термометричних матеріалів електронного та діркового типів провідності, що у 4÷6 підвищує чутливість існуючих перетворювачів. Створено та впроваджено термічно стабільні чутливі елементи електрорезистивних термометрів, що підвищує точність та розширяє діапазон температурних вимірювань. The thesis provides the justification and a new solution of an important scientific and technical problem of the development of the thermometry physical basis by introducing new sensitive elements of the temperature measurement means and the methods of their characteristics simulation, obtained on the basis of the latest thermometric materials with improved metrological and operational characteristics. The concept of simulation and obtaining of thermally stable sensitive elements of temperature measuring devices based on the latest thermometric materials obtained by alloying of semi-Heuser phases by developing an method for iterative simulation of structural, energy, thermodynamic and kinetic characteristics of thermal converters sensitive elements taking into account the results of experimental measurements of temperature dependences of the specific electrical resistance ρ, the coefficient of thermal-ers α and the magnetic susceptibility χ is substantiated and developed. Introduction of this method allows to significantly improve the efficiency of simulation of thermal converters sensitive elements thermometric characteristics, and the average value of the non-conformity coefficient of the experimentally obtained and predicted values of the electric resistance and thermo-ers in the temperature range of 4.2÷1300 K does not exceed ± 5%. A phenomenological model for the formation of thermally stable sensitive elements of thermal converters based on the latest thermometric materials is proposed, which ensures the stability of their energy and kinetic characteristics. The phenomenological model of its electronic structure, developed on the basis of the analysis of the sensitive element structure, explains the formation mechanism of the fundamental energy parameter of the semiconductor thermometric material – the band gap εg. In turn, knowledge of such a mechanism makes the ways of influencing the values of the electrical resistance and the thermo-ers clear at the stage of the formation of thermometric materials and allows to simulate and receive sensitive elements of thermal converters with predetermined properties. A method is developed for simulation of the kinetic characteristics of thermal converters new sensitive elements in a wide temperature range by calculating the distribution of the density of electronic states (DOS), the density of states at the Fermi level g (εF), the band gap band εg, the depth of the Fermi level εF, etc. The regularities of the transformation functions of sensitive elements of temperature measuring devices based on the latest thermometric materials in the temperature range of 4.2÷1300 K with improved metrological characteristics were established. A method of obtaining a thermoelectric pair of a thermoelectric thermometer sensitive element is proposed, both branches of which are made of the latest thermometric materials of electron and hole types of conductivity, which in 4÷6 increases the sensitivity of the existing thermocouples and expands the range of temperature measurements with one thermometer. The received sensory elements of thermoelectric converters are highly sensitive, and the ratio of changes in the values of thermo-ers to the temperature range is greater than all known industrial thermocouples. The method of obtaining of thermally stable sensitive elements of electrostatic thermometers from the latest thermometric materials is proposed, which significantly increases the accuracy and expands the range of temperature measurements. In addition, the temperature response coefficient of the received sensitive elements of the resistance thermometers is greater than the TRK of the metals, but is less in value of the TRK sensitive elements made from traditional semiconductors. At the same time, none of the known thermometers of resistance based on traditional semiconductors does not provide stability characteristics in the temperature range 4.2÷1300 K. Приведено обоснование и новое решение важной научно-технической проблемы развития физических основ термометрии путем внедрения новых чувствительных элементов средств измерения температуры и методов моделирования их характеристик, полученных на основе новейших термометрических материалов с улучшенными метрологическими и эксплуатационными характеристиками. Предложена концепция моделирования и получения термически устойчивых элементов средств температурных измерений на основе новейших термометрических материалов путем разработки алгоритма итерационного моделирования структурных, энергетических, термодинамических и кинетических характеристик новых чувствительных элементов преобразователей с учетом результатов эксперимента. Развит метод моделирования кинетических характеристик новых чувствительных элементов преобразователей в диапазоне температур 4,2÷1300 К. Установлены закономерности функций преобразования чувствительных элементов средств измерения температуры на основе новейших термометрических материалов в диапазоне 4,2÷1300 К с улучшенными метрологическими характеристиками. Получил развитие метод получения термоэлектрической пары термоэлектрического термометра, обе ветки которого изготовлены из новейших термометрических материалов электронного и дырочного типов проводимости, что в 4÷6 повышает чувствительность существующих преобразователей. Созданы и внедрены термически стабильные термоэлементы электрорезистивных термометров, что повышает точность и расширяет диапазон температурных измерений.
Development of the thermometry physical basis with the use of new sensitive elements of thermal converters
Развитие физических основ термометрии с применением новых чувствительных элементов термопреобразователей
Keywords: температура; чутливий елемент; термометр; термо-ерс; електроопір; temperature; sensitive element; thermometer; thermoelectric power; electrical resistance; температура; чувствительный элемент; термометр; термо-эдс; электросопротивление; 537.311.322